2008
DOI: 10.1007/s12275-008-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of secreted virulence factor genes by subinhibitory concentrations of antibiotics in Pseudomonas aeruginosa

Abstract: Recent studies have shown that subinhibitory antibiotics play important roles in regulating bacterial genes including virulence factor genes. In this study, the expression of 13 secreted virulence related gene clusters of Pseudomonas aeruginosa, an important opportunistic pathogen, was examined in the presence of subinhibitory concentrations of 4 antibiotics: vancomycin, tetracycline, ampicillin and azithromycin. Activation of gene expression was observed with phzAl, rhlAB, phzA2, lasB, exoY, and exoS. Subinhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 30 publications
(45 reference statements)
2
48
0
Order By: Relevance
“…Enhanced production of phenazines in response to subinhibitory concentrations of other antibiotics has already been reported (Mitova et al, 2008;Shen et al, 2008). Exposure to subinhibitory concentrations of colistin resulted in upregulation of the phenazine biosynthesis operon (Table 2).…”
Section: Physiological Consequences Of Colistin-induced Ahqssupporting
confidence: 52%
“…Enhanced production of phenazines in response to subinhibitory concentrations of other antibiotics has already been reported (Mitova et al, 2008;Shen et al, 2008). Exposure to subinhibitory concentrations of colistin resulted in upregulation of the phenazine biosynthesis operon (Table 2).…”
Section: Physiological Consequences Of Colistin-induced Ahqssupporting
confidence: 52%
“…In particular, at subinhibitory concentrations, many antibiotics appear to influence the expression of virulence factor genes, such as those for phenazine biosynthesis and regulation in pseudomonads (Cummins et al, 2009;Liang et al, 2008;Linares et al, 2006;Mitova et al, 2008;Shen et al, 2008;Skindersoe et al, 2008). The observations indicate that the effects of antibiotics may vary depending on the target bacterial species and the kind of antibiotic (Fajardo & Martinez, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…So far, an interpretation was only suggested for the effect of subinhibitory antibiotic concentrations on the triggering of virulence factor expression. Sensing such foreign toxic molecules would allow pseudomonas species to obtain increased fitness in a competitive environment (Cummins et al, 2009;Shen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among all virulence factors here investigated, may be the secretion of pyocyanin, an important molecule involved in P. aeruginosa's infection 9,[22][23][24][25] , was the more affected by dexamethasone. It was shown that even with a lower number of cells, biofilms under dexamethasone influence secrete higher amounts of this phenazine.…”
Section: Discussionmentioning
confidence: 95%
“…From our knowledge, only few groups are evaluating the interference of xenobiotics on pyocyanin secretion modulation. Shen et al 24 expressed their concern on the fact that sub-inhibitory concentrations of various antibiotics cause up-regulation on the expression of genes that codify the pyocyanin synthesis and it could complicate the antibiotic therapy expectatives. Other compounds such as curcumin 26 and salicylic acid 16 cause down-regulation on the genes with consequent virulence reduction.…”
Section: Discussionmentioning
confidence: 99%